The Arctic in Russia's Emergency Preparedness System - Elgsaas, Ingvill Moe (Arctic Review on Law and Politics, 2018)
Recent and projected developments in the Arctic call for improving emergency preparedness in the region. Arctic emergency preparedness is facing traditional challenges on a new scale as well as new, non-traditional challenges. There is political will on the part of Russian leadership to create a comprehensive emergency preparedness system in the Arctic, a system that integrates non-traditional alongside traditional emergency preparedness. This paper examines the formal institutional foundation for developing an emergency system in the Russian Arctic that includes counterterrorism as well as search and rescue and oil spill response. The paper concludes that the strengthening of Russian counterterrorism in recent years has produced a parallel specialized structure that operates autonomously and in isolation from the emergency preparedness structures responsible for handling traditional challenges. Differences between the national system for countering terrorism and the unified state system for prevention and liquidation of emergencies hinder comprehensive emergency preparedness in the Russian Arctic. That being said, there is considerable overlap in central actors between the two systems. This may serve as a window of opportunity for cooperation in Arctic emergency preparedness.